Occurrence and phylogenetic analysis of fowl adenovirus E in broiler flocks from Gaza Strip Palestine - Ahmed M Thabet; Ibrahim M Alzuheir; Adnan F Fayyad; Ahmed M Kheimar; Nasr H Jalboush (Journal of Infection in Developing Countries)
Introduction: Inclusion-body hepatitis (IBH) and hydropericardium syndrome (HPS) are highly infectious diseases caused by fowl adenoviruses (FAdVs). IBH and HPS cause major economic losses in poultry production. IBH is caused by multiple FAdV serotypes such as FAdV-11, FAdV8a, and FAdV8b; while HPS is mainly caused by the FAdV-4 serotype. In 2018, we detected FAdVs in West Bank - Palestine for the first time. This study aims to monitor the emergence of new FAdVs in broiler farms in Gaza Strip-Palestine in 2022.